DIPLOMASI PUBLIK INDONESIA KE MALAYSIA PASKA KEBIJAKAN PENENGGELAMAN KAPAL MALAYSIA DI LAUT INDONESIA - Umaya Bebi Imelda (Andalas Institute of International Studies, 2019)
This research aim to analyzes public diplomacy that is conducted by Indonesia to restore the positive image of Indonesia after the existence of ship sinking policy by Indonesia to foreign fishing boats originating from Malaysia. The Malaysian public began to respond to Indonesia related to the drowning of ships owned by Malaysian fisherman who is conducted illegal fishing in Indonesia. Malaysian public began to say that the policies imposed during the reign of President Joko Widodo is impressed arrogant, and do not look at a cognate country that is carried these of two countries. After a response from the Malaysian public, Indonesia began to try with public diplomacy to improve its image again. This research uses a descriptive methods. Researchers use the concept of public diplomacy proposed by Kishan S. Rana. There are 3 components, namely News Management, Country as Brand, and An Alternative Approach. In this research, Indonesia has conducted public diplomacy to Malaysia through news management in Indonesian media and Youtube, re-branding with Wonderful Indonesia, and alternative approach through cultural expo.